Cooling of advanced aircraft actuation systems - Gilson, Gareth M. (2012)
Electrical machines for aerospace applications often operate close to the allowable thermal limits due to high power density requirements. The power density of electrical machines is generally dependent on the machine and thermal management design. At flight level, a reduced pressure exists which in turn results in more challenging thermal management. Aerospace electric machine manufacturers are often limited with respect to the implemented cooling mechanisms. That is, natural convection systems are the norm, as fan cooled and fluid cooled machines may suffer from reliability issues.